Digital Organizational Culture and Human Resource Competence in Shaping Strategic Digital Marketing For Enhancing Marketing Performance in SMEs - Syti Sarah Maesaroh; Nugraha Adhi Pratama; Mohammad Affendy bin Arif (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Digital transformation is crucial for small and medium enterprises (SMEs) to remain competitive, but many face barriers in linking technology adoption to marketing performance due to resource constraints, technology adoption barriers, low digital competency, weak digital culture, and fragmented strategic execution.Purpose: This study examines how employee competencies and digital culture influence adaptive marketing strategies through social media and e-commerce and their implications, by adopting a theoretical dynamic resource and capability perspective.Design/methodology/approach: A survey of 900 randomly selected SME managers was conducted, and the data were analyzed using structural modeling to test for direct mediation.Findings/results: Results reveal that employee competence and digital culture drive adaptive marketing strategies, which in turn have the strongest impact on marketing performance. Marketing strategies act as a critical bridge between internal resources and market outcomes, highlighting the transformative role of strategic execution. The findings further indicate that digital culture alone does not directly enhance performance unless it is operationalized through structured and responsive digital marketing strategies.Conclusion: Unlike most prior studies that only examined direct links between resources and performance, this research integrates two theoretical perspectives and empirically demonstrates how intangible resources are transformed into marketing performance through adaptive digital strategies. The results provide important insights for SMEs in developing economies, where digital readiness varies across sectors and regions, emphasizing the importance of strategic alignment rather than mere digital adoption. Originality/value (State of the art): This study expands the research boundaries by highlighting the role of digital marketing strategies as a mediating mechanism in linking SMEs' internal capabilities with superior marketing performance. Keywords:   digital culture , social media, marketing performance, marketing strategy, SMEs